ANGKA KEJADIAN NEFROBLASTOMA BERDASARKAN USIA DAN JENIS KELAMIN PADA CT SCAN ABDOMEN DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM DAERAH DR. H. ABDOEL MOELOEK TAHUN 2015-2020 - Moch Rifly Hidayat; Alfi Wahyudi; Doni Rahman Nurdiana; Esteria Maharani; Toni Prasetia (CV. Jasa Sukses Abadi, 2023)
Nefroblastoma is one of the most common malignancies of primary kidney tumors in children, the incidence of nephroblastoma reaches 6-7% in cases of malignancy that occurs in children. To find out the incidence of nephroblastoma based on age and gender on an abdominal CT scan at the radiology installation at Dr.H. Abdoel Moeloek in 2015-2020. This study used a descriptive research design with retrospective method and cross sectional design. In this study, from 42 patients who were respondents, the most age group data were obtained at the age of 0-5 years with a total of 32 people with a percentage of 76.2%, followed by the age group of 6-10 years with 6 people with a percentage of 14.3% and the least was the age group of 11-15 years as many as 4 people with a percentage of 9.5%. In this study, the most common sex group was men with a total of 27 people with a percentage of 64.3%. In this study, there were 15 female respondents with a percentage of 35.7%. Obtained the age group, most at the age of 0-5 years with a total of 32 people with a percentage of 76.2%. Most of the sex group is male with a total of 27 people with a percentage of 67.6%.